Species diversity and secondary metabolites of Sarcophyton-associated marine fungi - Yuanwei Liu; Kishneth Palaniveloo; Siti Aisyah Alias; Jaya Seelan Sathiya Seelan (Molecular Diversity Preservation International, 2021)
Soft corals are widely distributed across the globe, especially in the Indo-Pacific region, with Sarcophyton being one of the most abundant genera. To date, there have been 50 species of identified Sarcophyton. These soft corals host a diverse range of marine fungi, which produce chemically diverse, bioactive secondary metabolites as part of their symbiotic nature with the soft coral hosts. The most prolific groups of compounds are terpenoids and indole alkaloids. Annually, there are more bio-active compounds being isolated and characterised. Thus, the importance of the metabolite compilation is very much important for future reference. This paper compiles the diversity of Sarcophyton species and metabolites produced by their associated marine fungi, as well as the bioactivity of these identified compounds. A total of 88 metabolites of structural diversity are highlighted, indicating the huge potential these symbiotic relationships hold for future research.